Exposure to strong irradiance exacerbates photoinhibition and suppresses N resorption during leaf senescence in shade-grown seedlings of fullmoon maple (Acer japonicum) - Kitao, Mitsutoshi; Yazaki, Kenichi; Tobita, Hiroyuki; Agathokleous, Evgenios; Kishimoto, Junko; Takabayashi, Atsushi; Tanaka, Ryouichi (Frontiers in Plant Science, 2022)
Leaves of fullmoon maple (Acer japonicum) turn brilliant red with anthocyanins synthesis in autumn. Based on field observations, autumn coloring mainly occurs in outer-canopy leaves exposed to sun, whereas inner-canopy leaves remain green for a certain longer period before finally turn yellowish red with a smaller amount of anthocyanins. Here, we hypothesized that outer-canopy leaves protect themselves against photooxidative stress via anthocyanins while simultaneously shading inner canopy leaves and protecting them from strong light (holocanopy hypothesis). To test this hypothesis, we investigated photoinhibition and leaf N content during autumn senescence in leaves of pot-grown seedlings of fullmoon maple either raised under shade (L0, ≈13 % relative irradiance to open) or transferred to full sunlight conditions on 5th (LH1), 12th (LH2), or 18th (LH3) Oct, 2021. Dry mass-based leaf N (Nmass) in green leaves in shade-grown seedlings was ≈ 30 mg N g-1 in summer. Nmass in shed leaves (25th Oct to 1st Nov) was 11.1, 12.0, 14.6, and 10.1 mg N g-1 in L0, LH1, LH2, and LH3 conditions, respectively. Higher Nmass was observed in shed leaves in LH2, compared to other experimental conditions, suggesting an incomplete N resorption in LH2. Fv/Fm after an overnight dark-adaptation, measured on 19th Oct when leaf N was actively resorbed, ranked L0: 0.72 > LH3: 0.56 > LH1: 0.45 > LH2: 0.25. As decreased Fv/Fm indicates photoinhibition, leaves in LH2 condition suffered the most severe photoinhibition. Leaf soluble sugar content decreased, but protein carbonylation increased with decreasing Fv/Fm across shade-grown seedlings (L0, LH1, LH2, and LH3) on 19th Oct, suggesting impaired photosynthetic carbon gain and possible membrane peroxidation induced by photooxidative stress, especially in LH2 condition with less N resorption efficiency. Although the impairment of N resorption seems to depend on the timing and intensity of strong light exposure, air temperature, and consequently the degree of photoinhibition, the photoprotective role of anthocyanins in outer-canopy leaves of fullmoon maple might also contribute to allow a safe N resorption in inner-canopy leaves by prolonged shading.